Thiolated pectin–doxorubicin conjugates: Synthesis, characterization and anticancer activity studies - Cheewatanakornkool, K.; Niratisai, S.; Manchun, S.; Dass, Crispin; Sriamornsak, P. (Elsevier, 2017)
© 2017 Elsevier Ltd In this paper, pectin was cross-linked by a coupling reaction with either thioglycolic acid or cystamine dihydrochloride to form thiolated pectins. The thiolated pectins were then coupled with doxorubicin (DOX) derivative to obtain thiolated pectin–DOX conjugates by two different methods, disulfide bond formation and disulfide bond exchange. The disulfide bond exchange method provided a simple, fast, and efficient approach for synthesis of thiolated pectin–DOX conjugates, compared to the disulfide bond formation. Characteristics, physicochemical properties, and morphology of thiolated pectins and thiolated pectin–DOX conjugates were determined. DOX content in thiolated pectin–DOX conjugates using low methoxy pectin was found to be higher than that using high methoxy pectin. The in vitro anticancer activity of thiolated pectin–DOX conjugates was significantly higher than that of free DOX, in mouse colon carcinoma and human bone osteosarcoma cells, but insignificantly different from that of free DOX, in human prostate cancer cells. Due to their promising anticancer activity in mouse colon carcinoma cells, the thiolated pectin–DOX conjugates might be suitable for building drug platform for colorectal cancer-targeted delivery of DOX.